Modelling the Effect of Partial Replacement of River Sand by Quarry Dust on Concrete Compressive Strength. - Woniala, Emma (Kabale University, 2024)
The depletion of river sand and its environmental impact has led to the exploration of alternative fine aggregates for concrete. This study investigates the use of quarry dust, a by-product of rock crushing, as a partial replacement for river sand in concrete. Experimental results demonstrate that replacing up to 45% of river sand with quarry dust optimally enhances compressive strength, achieving a maximum of 34.19 MPa. Beyond this optimum replacement level, the compressive strength begins to decrease. This reduction in strength is attributed to an increase in the quarry dust content, which results in higher water demand due to its finer particle size and greater water absorption, ultimately reducing the mix's workability. A regression model, fc = 26.21056 + 0.36698X − 0.00548X2 + 1.61314E-5X3, was developed to predict concrete strength based on the quarry dust content. The model's R-squared value of 0.9556 indicates a high level of correlation between the predicted and observed compressive strengths, confirming the reliability of the model in forecasting concrete performance with varying quarry dust proportions